Highly stable perovskite solar cells with an all-carbon hole transport layer. Issue 23 (27th May 2016) - Wang, Feijiu; Endo, Masaru; Mouri, Shinichiro; Miyauchi, Yuhei; Ohno, Yutaka; Wakamiya, Atsushi; Murata, Yasujiro; Matsuda, Kazunari
Abstract : A carbon hole conductive layer of SWNT/GO/PMMA can not only improve conversion efficiency but also stability in perovskite solar cells. Abstract : Nano-carbon materials (carbon nanotubes, graphene, and graphene oxide) have potential application for photovoltaics because of their excellent optical and electronic properties. Here, we demonstrate that a single-walled carbon nanotubes/graphene oxide buffer layer greatly improves the photovoltaic performance of organo-lead iodide perovskite solar cells. The carbon nanotubes/graphene oxide buffer layer works as an efficient hole transport/electron blocking layer. The photovoltaic conversion efficiency of 13.3% was achieved in the organo-lead iodide perovskite solar cell due to the complementary properties of carbon nanotubes and graphene oxide. Furthermore, the great improvement of photovoltaic performance stability in the perovskite solar cells using carbon nanotubes/graphene oxide/polymethyl methacrylate was demonstrated in comparison with that using a typical organic hole transport layer of 2, 2′, 7, 7′-tetrakis-( N, N -di-4-methoxyphenylamino)-9, 9′-spirobifluorene.